(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1987)
The early Gothic façade of Holyrood Abbey was originally distinguished by two large towers. Although many large churches built in the British Isles during the previous (12th) century had two western towers, they were generally built over the westernmost bays of the nave aisles. In the case of a few buildings dating to the later 12th and early 13th centuries, the towers flanked the last bays of the aisles, thereby creating a wide ’screen’ fagade. The position of the towers at Holyrood was distinctly different from either of these types. The towers were placed both outside the line of the aisle walls and in front of the plane of the west wall: they were tangent to the corners of the aisles by only one of their corners. As a result, a shallow open space was created between them, in front of the west portal. In this regard, Holyrood appears to have been exceptional in the British Isles. The closest parallels for this arrangement are found at several churches on the Continent which are widely separated geographically and, as a group, without any obvious connection with each other. The unusual system of passageways within the west front of Holyrood also further contributes to its unique character.